ANALISIS KEPERCAYAAN GENERASI MILENIAL TERHADAP LEMBAGA KEUANGAN SYARIAH - Emilia Septiani; Mulyadi Mulyadi; Sarifudin Serip (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
The purpose of this study is to analyze the trust of the millennial generation in Islamic financial institutions. The trust of the millennial generation refers to the principles of Good Corporate Governance (GCG) which consists of transparancy, accountability, responsibility, independence, fairness and sharia compliance. The data collection method used was the sample survey. The number of samples in this study was 150 samples. The sampling technique used in this study was accidental sampling. The analytical tool used is descriptive statistics. The results of this study indicate that the millennial generation's trust in Islamic financial institutions is high. This proves that the millennial generation in West Nusa Tenggara Province basically already has good trust in the operation of Islamic financial institutions.